Echolocation of Central Amazonian ‘whispering’ phyllostomid bats: call design and interspecific variation - Yoh, Natalie; Syme, Peter; Rocha, Ricardo; Meyer, Christoph F.J.; López-Baucells, Adrià (Mammal Research, 2020)
Phyllostomids (New World leaf-nosed bats) are the ecologically most diverse bat family and have undergone the most extensive adaptive radiation of any mammalian family. However comprehensive, multi-species studies regarding phyllostomid echolocation are scarce in the literature despite abundant ecological research. In this study, we describe the call structure and interspecific variation in call design of 40 sympatric phyllostomid species from the Central Brazilian Amazon, focussing on general patterns within genera, subfamilies and between feeding guilds. All but one species utilized short, broadband FM calls consisting of multiple harmonics. As reported for other bat families, peak frequency was negatively correlated with body mass and forearm length. Twenty-five species alternated the harmonic of maximum energy, principally between the second and third harmonic. Based on PCA, we were unable to detect any significant differences in echolocation call parameters between genera, subfamilies or different feeding guilds, confirming that acoustic surveys cannot be used to reliably monitor these species. We present Ametrida centurio as an exception to this generalized phyllostomid structure, as it is unique in producing a mono-harmonic call. Finally, we discuss several hypotheses regarding the evolutionary pressures influencing phyllostomid call structure. © 2020, The Author(s).
Keywords: Adaptive Radiation; Bat; Calling Behavior; Echolocation; Feeding Behavior; Interspecific Variation; Amazonia; Ametrida centurio; Chiroptera; Mammalia; Phyllostomidae